Pengaruh work pressure, job insecurity dan workplace favouritism terhadap turnover intention dengan taqwa sebagai variabel pemoderasi - Nurdianto, Wahid; Pratama, Abdul Aziz Nugraha (Journal of Management and Digital Business, 2021)
This study aims to answer the effect of work pressure, job insecurity and workplace favouritism on the turnover intention with taqwa as moderating variable. This research was conducted at PT Metinca Prima Industrial Works Salatiga. Data was collected by distributing questionnaires using an interval scale of 1-10 to 127 workers PT Metinca Prima Industrial Works Salatiga. The data analysis method used is multiple linear regression analysis. Testing the hypothesis shows that work pressure has no significant negative effect on turnover intention. Job insecurity does not affect turnover intention. Workplace favouritism has a positive and significant effect on turnover intention. Work pressure, job insecurity and workplace favouritism have a positive and significant effect on turnover intention. Taqwa can moderate the effect of work pressure on turnover intention. Taqwa can moderate the effect of job insecurity on turnover intention. Taqwa can moderate the effect of workplace favouritism on turnover intention.